The Relationship between Socio Cultural Background and Sport Achievement. (March 2017) - Sunarno, A; Syaifullah, R; Sihombing, D
Abstract: The aim of this research was to find out the relations between social cultural background of people of North Sumatera province in Indonesia (helper, show off, dominate, self-ego, hard worker, independent) in relation to sport achievement. This research used descriptive method by reviewing existing literature. Sample of this research was 1072 athletes from 34 different group of sport that have been participating in National Sport Competition (PON) in years 2004, 2008, 2012, 2016. The result shows that nine different kinds of self-defence group have been chosen by 291 athletes such as: fencing, wrestling, Judo, Karate, Pencak Silat, Taekwondo, Tarung Derajat, Boxing and Whusu. In contrast, 781 athletes preferred to another kinds of sport than self-defence, 148 for measurable sport, 143 for accuracy sport, and 490 for games sport group. Eventually, self-defence athletes always contribute highest medals in each national sport competition event. In conclusion, the research shows that social-cultural background of people of North Sumatera has significant relationship to the sport achievement. The implication of research's results can be utilized as a basic talent scouting and talent development for determining young talented athletes in North Sumatera.